Contourlet transform with modified particle swarm optimisation for despeckling and feature enhancement of SAR images. (10th April 2015) - Shanthi, I.; Valarmathi, M.L.
This paper gives a contourlet transform with modified PSO (MPSO) for the feature enhancement, edge preservation and despeckling of SAR images. In this paper, despeckling and preservation of edges are combined with improved gain function that optimises the contourlet coefficients for the enhancement of quality of denoised image. Furthermore, global search algorithm such as MPSO algorithm is applied for the best result. Increase in convergence speed and reduction in premature convergence are possible with MPSO that produces new learning scheme and a mutation operator. Contourlet transform with MPSO is compared with some of the standard speckle reduction filters and wavelet transform with MPSO. Experimental results show that the contourlet transform with MPSO gives better quality of image.